PENGARUH SUPLEMENTASI ETHINYL ETHYL ESTRADIOL TERHADAP HISTOPATOLOGIS GINJAL TIKUS OVARIEKTOMI - , NURUL ARIFAH; , Dr.drh.Hartiningsih, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ovariectomy decrease the production of estrogen hormone resulted in an increase in the calcium excretion through kidney. Supplement estrogen, increase estrogen and decrease calcium excretion of urine, however supplement estrogen also decrease parathyroid hormone and increase calcium excretion of urine. This research aimed to know the description of histopatologis kidney of rats ovariektomi who consumed supplement of ethinyl ethyl estradiol. Ten female wistar rats aged eight weeks were divided into 2 groups, rat ovariectomy (OVK) and mouse ovariectomy which fed supplement of ethinyl ethyl estradiol 25 g/rats/day orally (OVE). Each five rats, fed with standard woof and drinking water aquabidestilata in ad libitum. Rats placed in an individual cage with 22-25 of room temperature. Rats adapted to woof and environment for one week, at the age of nine weeks, performed ovariektomi surgery. One week after surgery, all of the mice were given treatment during eight weeks. In the end of treatment, rats were euthanized and taken the sinister kidney for histopatologi check up with painting of HE than analyzed by descriptive. The result showed that there is no change on the illustration of histopatologiskidney of rats ovariectomy who fed with supplement of ethinyl ethyl estradiol. From the result of the research, concluded that ethinyl ethyl estradiol is save against the kidney function. Keywords: Ethinyl ethyl estradiol, kidney, ovariectomy